Pendampingan Peningkatan Maharah Kalam Santri melalui Panggung Kreasi Bahasa Arab Lailah Arabiyah di Pondok Pesantren Darun Nuhat Lamongan - Nisa', Khoirun; Nabilah, Isti’anah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Seeing the potential that the students of the Darun Nuhat Islamic Boarding School have in reading, speaking and composing stories in Arabic, there is a need for a forum for the students to improve their Arabic language skills. One of the potentials that will be improved in this mentoring process is the ability to speak Arabic or known as maharah kalam. This mentoring is realized in the form of guidance, guidance and talent training and the targets in this mentoring process are the students of the Darun Nuhat Islamic Boarding School, so that the maharah kalam potential possessed by the students will develop and improve in quality. This mentoring uses the PAR (Participatory Action Research) approach method, which involves carrying out research to define a problem and applying information into action as a solution to a problem that has been defined. The steps taken in the mentoring process increase the students' potential for maharah kalam. through the Lailah Arobiyah Arabic language creation stage, namely: 1. Problem Identification, 2. Pproblem solving, 3. Action as solution, 4. Lastly , giving appreciation. With this assistance, the students will realize their potential and be more enthusiastic about innovating and being creative according to their respective talents